Analysis Of Business Feasibility Study on Dapur Ra Donut Business - Athifa Faizatul Azkiya; Ahyakudin (EBIZER: Jurnal Ekonomi, Manajemen, Akuntansi, dan Bisnis, 2026)
A business feasibility study is an important tool for assessing the potential and sustainability of a business, especially for culinary MSMEs facing competitive market competition. This study aims to evaluate the feasibility of Donat Dapur RA's business from market, technical, management, financial, risk, and environmental aspects, and to provide recommendations for development strategies. The research method used is descriptive qualitative with data collection through interviews with the business owner, production process observations, and literature studies. The analysis results show that Donat Dapur RA has stable demand, competitive prices, consistent product quality, and adequate production capacity. The management structure is simple but effective, although it needs to improve SOPs and bookkeeping. Financially, the business is very feasible with a net profit of approximately IDR 3,000,000 per month, an NPV of IDR 121,188,000, an IRR of 236%, a PI of 8.94, and a payback period of approximately five months. Operational and market risks can be managed through simple mitigation and digital marketing strategies. Environmental impact is relatively low with simple but effective waste management. In conclusion, Donat Dapur RA is feasible to run and has long-term development prospects, and the results of this study can be a reference for MSMEs in realistic and sustainable business planning.